2022
DOI: 10.3390/microorganisms10020426
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasitoses in a Non-Endemic Setting during a 10-Year Period (2011–2020): A Focus on Dientamoeba fragilis

Abstract: Dientamoeba fragilis is a cosmopolitan and neglected protozoan. Although little is known concerning its pathogenicity and its true prevalence worldwide, its role as enteric pathogen is emerging, as the occurrence of dientamoebiasis has increased also in industrialised countries. This study investigated the occurrence and prevalence of intestinal parasites, focusing on D. fragilis in a 10-year period (2011–2020) in a single tertiary-care hospital located in Northern Italy. A statistical evaluation of the correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The lack of reports for D. fragilis and P. hominis reflects the poorly defined pathogenicity of these species so further investigation into the occurrence of symptomatic cases after the consumption of contaminated food or water should be considered [21,284,286].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of reports for D. fragilis and P. hominis reflects the poorly defined pathogenicity of these species so further investigation into the occurrence of symptomatic cases after the consumption of contaminated food or water should be considered [21,284,286].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on this protozoan parasite were conducted in industrialized countries and prevalence values ranged between 0.3% and 82.9%. The few studies available for developing countries reported prevalence values between 0% and 60.6% [39,284]. Spreading by the fecal-oral route is most likely though zoonotic transmission was also suggested since D. fragilis was detected in pigs, cats, and dogs [21].…”
Section: Dientamoeba Fragilismentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show a prevalence of 24% in gut-healthy people in different age groups, which is slightly lower than in the above-mentioned studies. Interestingly, a ten-year study conducted at the University Hospital of Parma demonstrated an almost comparable prevalence of D. fragilis (i.e., 20%) in patients with gastrointestinal symptoms [ 3 ]. Following data from patient cohorts and healthy subjects, the incidence of D. fragilis seems to be more or less comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Dientamoeba fragilis is a human intestinal protist with cosmopolitan distribution and prevalence ranging from 0.2% to 82% (reviewed in [ 1 , 2 , 3 ]). Most studies addressing its occurrence are from high-income countries and surprisingly, less is known from low-income countries [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%